Kualitas Ikan Lele Dumbo (Clarias Gariepinus) Asin Kering Menggunakan Metode Dry Salting dan Wet Salting Dengan Konsentrasi NaCl Yang Berbeda - Zainal Muhtadi; Wehandaka Pancapalaga; Mochammad Wachid (Food Technology and Halal Science Journal, 2019)
The production of catfish in East Java in recent years increased significantly from 96,337.2 tons in 2014, to 113,070,4 tons in 2015. The high production impact on difficulties of farmers in some areas in marketing their crops, consequently many farmers lose money because feedstocks continue to go while the harvest difficulties sales. One way to increase market interest is by processing it into salted fish products trough salting method, there are two kinds of salting methods, including Wet salting and Dry salting. However, not all salting techniques produce a guaranteed quality product, this is due to the absence of a definite dose for the number of ingredients used, so determining the right NaCl concentration is essential to create a high quality dried salted fish product. The aim of this research is to know the effect of Salting method and different NaCl concentrations on the quality of dried catfish. This research uses the experimental method with Randomized Block Design (RBD) pattern factorial. The factor I: salting method consisting of Z1: Dry salting Z2: Wet salting. Factor II: NaCl concentration consisting of M1: 15%, M2: 25%, M3: 35%, M4: 45% So that there are 8 treatment variables, and each repeated 3 times so that there are 24 treatments. The parameters tested include NaCl, water, ash insoluble in acid, total plate count, protein, fat, and organoleptic (taste, appearance, aromatic, texture). The results of this study indicate that there is an interaction between the use of different types of salt methods and NaCl concentration on NaCl content, water, ash insoluble in acid, total plate count, and organoleptic taste. But there is no interaction with parameters protein, fat, organoleptic appearance, aromatic, and texture. Based on the Physico-chemical and organoleptic properties of dried salted catfish we found the best total treatment on Z1M4 (Dry salting: NaCl 45% concentration) with NaCl 15.44%, Water 16.67%, Ash Insoluble in Acid 0.21%, Total Plate Count 1.1 x 104, Protein 25.27%, Fat 6.06%, Organoleptic (taste) 5, Organoleptic (Appearance) 7.08, Organoleptic (Aromatic) 6.92, Organoleptic (Texture) 7.67.